Analisis Ketepatan Kodefikasi Penyakit Berdasarkan Pengetahuan Petugas Kesehatan: Analysis of Disease Coding Accuracy Based on Healthcare Workers’ Knowledge - Soraya, Soraya; Adawiyah, Rabiatul; Heriyadi, M.; Cantika, Rahardina Dwi (Chakra Brahmanda Lentera Institute, 2026)
Accurate disease coding is a crucial component of health information systems, as it plays an essential role in morbidity data compilation, healthcare service reporting, insurance claim processes, and decision-making in healthcare facilities. With the increasing demand for accurate health data, proper disease coding has become increasingly important, including at the Brimob Clinic of the South Kalimantan Regional Police, which provides healthcare services for police personnel and their families. Inaccurate diagnostic coding may lead to errors in case documentation, administrative delays, and potentially compromise the quality of health program planning and evaluation. Therefore, this study aimed to analyze the accuracy of disease coding and examine the role of healthcare workers’ knowledge as a determining factor. This study employed a quantitative approach with a cross-sectional design. The respondents were healthcare workers directly involved in diagnostic documentation and disease coding at the Brimob Clinic of the South Kalimantan Regional Police. The independent variable was healthcare workers’ knowledge of disease coding based on ICD-9 and ICD-10, while the dependent variable was the accuracy of disease coding. Data were collected using a standardized knowledge questionnaire and medical record document audits to assess the consistency between medical diagnoses and the assigned disease codes. The results showed that healthcare workers’ knowledge levels varied, and discrepancies between medical diagnoses and recorded disease codes were still identified. Statistical analysis using the Spearman rho test revealed a significant association between healthcare workers’ knowledge and the accuracy of disease coding, indicating that higher knowledge levels were associated with more accurate diagnostic coding. This study concludes that healthcare workers’ knowledge plays a vital role in ensuring accurate disease coding. These findings imply the need for continuous coding training and the development and implementation of clear standard operating procedures (SOPs) to improve coding accuracy. Enhancing disease coding quality is expected to support accurate medical record documentation and strengthen health program management at the Brimob Clinic of the South Kalimantan Regional Police.